2017
DOI: 10.3168/jds.2016-12262
|View full text |Cite
|
Sign up to set email alerts
|

Key role of short-chain fatty acids in epithelial barrier failure during ruminal acidosis

Abstract: Subacute ruminal acidosis is induced by high concentrations of short-chain fatty acids (SCFA, mainly acetate, propionate, and butyrate) that release protons to decrease the pH of the ruminal digesta. This low pH, in turn, is thought to damage epithelial barrier function. The present study applied a model of simulated ruminal acidosis ex vivo to investigate if SCFA directly contribute to epithelial barrier failure beyond their role as proton donors. Epithelial tissues from the rumen of slaughtered sheep were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 55 publications
4
54
1
1
Order By: Relevance
“…Alterations in J fluor and G t are commonly used to assess the permeability of the paracellular space to large ( J fluor ) and small ions ( G t ), assuming that the transcellular route has negligible ( J fluor ) or rather constant ( G t ) contribution to these functional barrier readouts. Nevertheless, we have demonstrated in previous studies that fluorescein is also able to use the transcellular route for permeation across RE, for example, after an acid challenge (Greco et al, ; Meissner et al, ). Based on the fact that G t and the protein expression of all tested TJ proteins were unchanged by GLP‐1 and GLP‐2 in the present study, we thus propose that paracellular barrier function of RE was not affected by these hormones during the 7‐hr incubation, despite the fact that J fluor was changed in the last flux period by either of them.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Alterations in J fluor and G t are commonly used to assess the permeability of the paracellular space to large ( J fluor ) and small ions ( G t ), assuming that the transcellular route has negligible ( J fluor ) or rather constant ( G t ) contribution to these functional barrier readouts. Nevertheless, we have demonstrated in previous studies that fluorescein is also able to use the transcellular route for permeation across RE, for example, after an acid challenge (Greco et al, ; Meissner et al, ). Based on the fact that G t and the protein expression of all tested TJ proteins were unchanged by GLP‐1 and GLP‐2 in the present study, we thus propose that paracellular barrier function of RE was not affected by these hormones during the 7‐hr incubation, despite the fact that J fluor was changed in the last flux period by either of them.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, we have demonstrated in previous studies that fluorescein is also able to use the transcellular route for permeation across RE, for example, after an acid challenge (Greco et al, 2018;Meissner et al, 2017). Based on the fact that G t and the protein expression of all tested TJ proteins were unchanged by GLP-1 and GLP-2 in the present study, we thus propose that paracellular barrier function of RE was not affected by these hormones during the 7-hr incubation, despite the fact that J fluor was changed in the last flux period by either of them.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These data suggested that higher expression of IGFBP5 in rumen papillae is associated with the changes of the fermentation in rumen. Higher expression of IGFBP5 in rumen papillae might be necessary for adaptation to highly fermentable diet causing disruption of rumen epithelial barrier (Greco et al, 2018;Meissner et al, 2017;Steele et al, 2011). IGFBP5 induced monocyte migration in lung epithelium in mice (Yasuoka, Yamaguchi, & Feghali-Bostwick, 2009).…”
Section: Discussionmentioning
confidence: 99%